The influence of fuel additives SO-2E on diesel engine exhaust emission - Labeckas, Gvidonas; Slavinskas, Stasys (Transport, 2003)
One of the methods that allows substantially to reduce exhaust smoke of diesel engines and avoid possible damage of the environment by harmful emissions is the usage of multipurpose fuel additives. The efficiency of new Estonian made fuel additives SO-2E, that have been introduced recently for the experts attention, was investigated in small heating boilers and low-powered ships. The purpose of this research is to determine the influence of fuel additives SO-2E on the performance of a high-speed direct injection diesel engine in order to evaluate some of quantitative composition changes of the exhaust gases especially environmentally harmful nitrogen oxides, carbon monoxides and smoke emissions. Bench tests have been performed on the four-stroke, four-cylinder, water-cooled direct injection diesel engine D-243 with splash volume Vl = 4,75 dm3 and compression ratio ɛ = 16:1. Test results show that the application of diesel fuel additives SO-2E in proportion 1:500 (0,2 % by volume) at engine rated power reduces nitrogen monoxides NO and common NOx emission by 11,54 and 9,64 % respectively, however the amount of NO2 in totally diminished background of nitrogen oxides increases by 7,39 %. On the other hand, when running the engine at moderate (bmpe = 0,35 MPa) load, the fuel additives reduce emissions of all nitrogen components – NO by 16,1%, NO2 by 11,8% and NOx by 15,7%. The influence of fuel additives on the amount of carbon monoxides in the exhausts seems to be more complicated. At engine rated speed/power fuel additives increase CO emission by 12,5%, but as soon as engine load increases and revolution frequency drops down to the maximal torque area n = 1600–1800 min-1, they reduce the amount of CO in the exhaust gases on the average 20–28%. It is important to notice that the changes in the smoke emission remain in close association with CO emissions. At certain revolution frequencies and moderate load the fuel additives SO-2E lead to noticeable reduction of the exhaust smoke, however at engine rated power and speed the smoke emission is obtained approximately 5–10% higher. In spite of dissimilar influence of the fuel additives SO-2E on the quantities of CO produced and exhaust smoke it would be worth to apply them in high-speed DI diesel engines in order to reduce nitrogen oxides NOx emission. First Published Online: 19 Dec 2011